Management of Critically Ill Obstetric Patients Admitted in Intensive Care Unit of Enam Medical College Hospital, Savar, Dhaka - Khanum, Easnem; Ara, Gulshan; Islam, Md Ashraful (Journal of Enam Medical College, 2024)
Background: Pregnancy related complications are more observed in developing countries than developed countries and sometimes need intensive care support to reduce both morbidity and mortality. Any critical condition with acute respiratory failure or hemodynamic insufficiency are the main cause of admission. The management is a great challenge as it is a little bit different from other critically ill patient, should give emphasis on several factors for the fetomaternal wellbeing and needs multidimensional approach. Objectives: The aim of our study was to evaluate the indication of critically ill obstetric patients needed to intensive care support, to assess the fetomaternal outcomes and to observe the applications of different types of interventions needed for the management of these cases. Materials and Methods: A retrospective study was conducted at Enam Medical College Hospital in Bangladesh, with 105 critically ill obstetrics patient admitted in ICU during the period of June 2014 to December 2017. Patients requiring advanced respiratory or ventilator support or needed care of two or more organ system support were fulfilled the criteria for ICU admission. Data were collected from the medical records of Obstetric and Intensive care unit in a preformed sheet, analyzed by SPSS 20.0. ''p'' value of ≤ 0.05 is considered as statistically significant. After admission to the ICU primary resuscitation was done at first then several types of intervention were done immediately as per ICU protocol. Management was done by multidisciplinary approach. Result: Total 105 critically ill obstetric patients were admitted which corresponds 2.66 % of the total ICU admission. Referral cases from outside of the hospital was found 60.95%. Postnatal cases were found 71.42% more than antenatal (28.58%). The most common indication for ICU admission was found as obstetric hemorrhage (50.47%) and hypertensive disorders (32.38%). 49.5% patients needed mechanical ventilation, 57.14% needed ionotropic supports, 85.05% needed transfusions of either blood or blood products, 7.02% needed hemodialysis. Most of the patients (46) were stayed up to 2 days, a few (10) stayed more than 7 days, 26 were stayed 2−3days and 23 were stayed for 3 to 5 days. The maternal death was observed in 25.71% among them most of the cases were due to delayed referral case (77.7%). Conclusion: Obstetric hemorrhage is the most common cause of ICU admission. Early transfer to the ICU may reduce maternal death. Maternal death more found in referral cases. High dependency unit may reduce ICU admission. J Enam Med Col 2022; 12(1): 9−16